Smoking relapse and weight gain prevention program for postmenopausal weight-concerned women: A pilot study. (August 2015) - Copeland, Amy L.; McVay, Megan A.; Martin, Pamela D.; Rash, Carla J.; Kendzor, Darla E.; Baillie, Lauren E.; Spears, Claire A.; Geiselman, Paula J.
Abstract: Objective: Postmenopausal women have substantial concerns about weight gain when quitting smoking, which may contribute smoking relapse. There is a need for smoking cessation and weight gain prevention programs effective in this population. Methods: Two formats of a smoking cessation/weight gain prevention follow-up intervention in postmenopausal weight concerned women were compared: a minimally-tailored group format and a highly tailored, multidisciplinary individual format. Effects on sustained abstinence and postcessation weight gain were assessed. Postmenopausal smokers received 6 sessions of behavioral counseling over a 2-week period, 8 weeks of the nicotine transdermal patch, and subsequent random assignment to receive follow-up relapse prevention sessions at 1, 3, 8, and 16 weeks postcessation in either group or individual format. Results: The sample ( N  = 98) was 67% Caucasian and 33% African-American. Age: m  = 52.3 (7.8) years, follicle stimulating hormone: m  = 42.6 (25.7), body mass index (BMI): m  = 27.4 (6.2), daily smoking rate: m  = 20.3 (11.5), for m  = 29.4 (10.7) years, Fagerström Test for Nicotine Dependence (FTND): m  = 6.4 (2.1), and carbon monoxide: m  = 23.8 (13.0) ppm. Abstinence rates in the group condition were significantly higher at 8 weeks posttreatment. Group format significantly predicted abstinence rates at 8 and 16 weeks posttreatment, even while controlling for age, race, BMI, CPD, years smoking, FTND, and weight concern. Weight concern predicted postcessation weight gain at 8 and 16 weeks posttreatment. Conclusions: Results indicate that smoking cessation programs for postmenopausal women may best be delivered in a group format and that postcessation weight concerns be dealt with prior to a quit date. Highlights: Group format produced significantly higher rates than individual sessions of continuous abstinence at 8 weeks. Peer support may be particularly important for cessation efforts with postmenopausal smokers. Pretreatment weight concern predicted weight gain regardless of session format. Addressing weight concern is critical for older/postmenopausal weight concerned smokers.